Oral Microbiota: As a Cause of Head and Neck Cancers - Efsun Somay; Busra Yilmaz; Erkan Topkan; Ahmet Kucuk; Berrin Pehlivan; Ugur Selek (Perspective of Recent Advances in Medical Research Vol. 11, 2023)
Head and neck squamous cell cancers are a significant source of cancer-related morbidity and mortality worldwide (HNSCC). Risk factors like geographic differences, genetic predisposition, gender, age, type of diet, smoking and/or alcohol consumption habits, and sexual preferences may play a role in the etiology of HNSCC, depending on the site that is affected. Another hypothesis for the cause of HNSCC is dysbiosis. Over 700 symbionts and pathogenic microbial species can be found in the oral microbiota. By causing chronic inflammation and creating an immune-suppressed microenvironment that promotes cell proliferation and inhibits apoptosis, disruption of the healthy balance of the oral microbiota sets off the carcinogenic mechanisms (Fig. 1). With well-established links between the oral microbiota and chronic inflammation and cell proliferation, recent studies have discovered that individuals with the human microbiome are linked to a variety of cancer types. The bacterial genome, toxins, and metabolites have also been proposed as additional causes or enablers of carcinogenesis and its progression in the head and neck region in addition to chronic inflammation. But it’s still not entirely clear what the exact mechanisms are. However, a deeper comprehension of the underlying mechanisms might result in the creation of brand-new preventive or specialized therapies that can be applied in standard clinical practice. A recent and well-received topic in the oncological and dental communities is the connection between oral dysbiosis and the emergence of HNSCC. As a result, this chapter aims to present a thorough overview of the information that is currently available on the potential mechanistic connections between alterations in the oral microbiota and the emergence of HNSCC, which is still in the research phase.